Gender Differentials in Perception of Women Participation in Political and Community Development in Ogun East Senatorial District, Nigeria - Iyunade, Olufunmilayo Toyin (NIU Journal of Humanities, 2020)
This study investigated the differentials in perception of gender on women participation in politics and community development in Ogun East Senatorial District, Nigeria. A questionnaire tagged labelled â€œwomen participation in politics and community development questionnaireâ€ was administered on one hundred and seventy-two (172) political and career office holders in the study area. Inferential statistical of t-test was used to analyse the data collected. Findings revealed that significant differences exist in the perception of male and female respondents as to the number of women voted into elective offices; the level of women participation in decision-making; and outcome of women appointed into political offices. On the basis of the findings, recommendations were made for greater involvement of women in politics and community development. Keywords: Gender, women, participation, perception, community, development